Analysis of germline CDKN1C (p57KIP2) mutations in familial and sporadic Beckwith-Wiedemann syndrome (BWS) provides a novel genotype-phenotype correlation. Issue 7 (1st July 1999) - Lam, Wayne W K; Hatada, Izuho; Ohishi, Sachiko; Mukai, Tsunehiro; Joyce, Johanna A; Cole, Trevor R P; Donnai, Dian; Reik, Wolf; Schofield, Paul N; Maher, Eamonn R
Abstract : Beckwith-Wiedemann syndrome (BWS) is a human imprinting disorder with a variable phenotype. The major features are anterior abdominal wall defects including exomphalos (omphalocele), pre- and postnatal overgrowth, and macroglossia. Additional less frequent complications include specific developmental defects and a predisposition to embryonal tumours. BWS is genetically heterogeneous and epigenetic changes in the IGF2/H19 genes resulting in overexpression of IGF2 have been implicated in many cases. Recently germline mutations in the cyclin dependent kinase inhibitor gene CDKN1C (p57 KIP2 ) have been reported in a variable minority of BWS patients. We have investigated a large series of familial and sporadic BWS patients for evidence of CDKN1C mutations by direct gene sequencing. A total of 70 patients with classical BWS were investigated; 54 were sporadic with no evidence of UPD and 16 were familial from seven kindreds. Novel germline CDKN1C mutations were identified in five probands, 3/7 (43%) familial cases and 2/54 (4%) sporadic cases. There was no association between germline CDKN1C mutations and IGF2 or H19 epigenotype abnormalities. The clinical phenotype of 13 BWS patients with germline CDKN1C mutations was compared to that of BWS patients with other defined types of molecular pathology. This showed a significantly higher frequency of exomphalos in the CDKN1C mutation cases (11/13) than in patients with an imprinting centre defect (associated with biallelic IGF2 expression and H19 silencing) (0/5, p<0.005) or patients with uniparental disomy (0/9, p<0.005). However, there was no association between germline CDKN1C mutations and risk of embryonal tumours. No CDKN1C mutations were identified in six non-BWS patients with overgrowth and Wilms tumour. These findings (1) show that germline CDKN1C mutations are a frequent cause of familial but not sporadic BWS, (2) suggest that CDKN1C mutations probably cause BWS independently of changes in IGF2/H19 imprinting, (3) provide evidence that aspects of the BWS phenotype may be correlated with the involvement of specific imprinted genes, and (4) link genotype-phenotype relationships in BWS and the results of murine experimental models of BWS.